Reframing Primary School Management through Glocalization: Integrating Religious Character and Global Citizenship Education - Alfi Muhimmah, Hitta; Saadatul Ummah, Fiena; Fakhrudin, Ali; Ikhlasiah Rahman, Delfia; Supriyanto, Supriyanto; Mawaddah, Nurhayati; Syariffanor binti Hisman, Ts. (IJORER : International Journal of Recent Educational Research, 2026)
This study reconceptualizes primary school management by advancing glocalization from a pedagogical notion to a structural governance paradigm that integrates religious character formation and global citizenship competence within a coherent system. Using a research and development design based on the ADDIE framework, the study involved systematic needs analysis, expert validation, pilot implementation, and multi-source evaluation through quantitative and qualitative approaches. The developed model achieved very high validity (95%) and strong practicality (90%), indicating both conceptual robustness and contextual feasibility. Empirical implementation produced measurable improvements in students’ religious character (15.3%) and global competence (13.8%), with overall effectiveness ranging from 88% to 90%, demonstrating that integration operates at a systemic rather than symbolic level. Unlike conventional models that treat character education and global competence as fragmented or curriculum-bound elements, this study embeds both within school governance structures, positioning religiosity as the ethical foundation of leadership and global competence as the strategic orientation of institutional practices. By relocating integration from classroom-level intervention to organizational design, the study contributes to the advancement of value-based school governance theory and offers a scalable framework for addressing the persistent tension between local identity and global demands in contemporary education systems.